MEMBEDAH DIALOG ACARA DUA SISI “UU ORMAS MENCIDERAInDEMOKRASI?” DENGAN TEORI BREAK DAN PENDEKATAN LINGUISTIK FORENSIK: KAJIAN POLITIK HUKUM - Astuty; Susilowati, Tri (Judge : Jurnal Hukum, 2024)
A crime is not just a physical force, it will still be a crime can also be done through language. Forensic linguistics is a language science that analyzes crime in terms of what criminals are used. the research in this article discusses a two-sided event with the theme of "ORMAS legislation offending democracy?" the data in this study is the speech of the source and also the text of ORMAS law which will be discussed with the main theory of BREAK and the supporting theories is the theory of leniency in language and also policy analysis in forensic linguist's view.